Analisis Faktor Penghambat Ekonomi Keluarga Nelayan Wilayah Pesisir Desa Bagan Percut, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara - Agustina Rahayu Sianturi; Aprilia Zaeni Rapiah; Muhammad Najmul Fahmi; Vadillah Raihto Hutasuhut; Tumiar Sidauruk (Journal on Education, 2024)
The aim of this research is to analyze the economic inhibiting factors for fishing families in the coastal area of ​​Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. This research uses data analysis methods. Research results show that access to financial capital is one of the main challenges for fishermen in this region. The majority of fishermen depend on a loan system from local middlemen or "toke", which often provides fish selling terms and prices that are less favorable for fishermen. This causes fishermen to be trapped in a cycle of poverty and prolonged economic difficulties. The low level of education among fishermen has a significant impact on their ability to manage fisheries efficiently and increase the added value of their catch. Lack of knowledge and skills in post-harvest handling, marketing, and the adoption of modern fishing technology and practices are major obstacles in efforts to increase fishermen's productivity and income. Unpredictable weather conditions, limited access to modern technology and equipment, competition with large fishing industries, unsustainable natural resource management, and inadequate infrastructure are also significant economic inhibiting factors for fishing families in the Coastal Area of ​​Bagan Percut Village.